Digit ratio effects between expertise levels in American Football players - Schorer, J.; Rienhoff, R.; Westphal, H.; Baker, J. (Talent Development & Excellence, 2013)
Previous research highlights the association between 2D:4D and performance in a host of elite sports. This study compared several variables compared to the 2D:4D ratio among American football players of different skill levels. One-factorial analyses of variance between four groups were used. Participants came from four teams from different American Football leagues in Germany i.e., teams from the first (n=17), second (n=24), fourth (n=18) and fifth (n=20) leagues. Digit ratio was measured from digital images and t-test and analyses of variance were used to explore differences between teams and compared to normative data. The athlete sample had significantly lower 2D:4D ratio than the normative data. Further, there were significant differences for the left hand and the delta of the digit ratios of both hands but no effect for the right hand. These results add additional support for general effects for both digit ratio in elite sport; however, they also point to several areas of future research.